PRAKTIK REKAYASA DISPENSING PUMP SPBU PERSPEKTIF PERUNDANG-UNDANGAN DAN HUKUM ISLAM - Hazar Kusmayanti; Ratu Chairunissa (Asy-Syari'ah, 2020)
Abstract: This research aims to examine and analyze the responsibilities of petrol stations as well as legal protection that can be obtained by consumers designed by petrol stations based on statutory views and Islamic law. This study uses the Normative Juridical method with references to Law Number 8 of 1999 concerning Consumer Protection and Law Number 2 of 1981 concerning Legal Metrology regarding measuring instruments. These results conclude that: First, engineering pump removal by business actors carried out by SPBU managers has an impact on the revocation of the PASTI PAS predicate by Pertamina which has harmed consumers, so that it is the responsibility of business actors who provide compensation in accordance with Article 19 of the Consumer Protection Law because it has increased to default. Furthermore, in Islamic law, the stipulation of compensation is carried out because no loss or damage to the victim has occurred. Second, legal protection for consumers, namely in the form of preventive and repressive. Preventive measures are carried out by providing guidance by the government and Pertamina, while repressiveness is carried out by law enforcement and / consumer dispute resolution both through courts and outside the court. Likewise, the Islamic view of pump engineering is not in line with the principles and principles of Islamic law because there is an element of gharar in it.